Fish ball maker machine - Zulkarnain, Muhammad Harith Ifwat; Mohd Nazaruddin, Nur Azieyana; Zulkipli, Mohd Fazli; Ismail, Nurul Syahira; Hassan, Mohd Fahrul; Mohd Gaus, Nur Farah Hanan; Abdul Omar, Nurzhatul Aziemah (Penerbit UTHM, 2017)
Fish balls are common food in southern China and Chinese communities mostly cannot resists from "fish paste". Asian meatballs differ significantly in texture from their European counterparts. Instead of being ground, the fish is pounded, giving it a smooth texture. Pounding, unlike grinding, uncoils and stretches previously wound and tangled protein strands in the meat. In today’s markets where customers crave for variety product, innovation is the way to go. In today’s markets the fish ball machine has been designed in big size and is not suitable for homemade fish balls. Besides, the machine is more expensive and not affordable for household. So, it is not suitable to be placed at home and it is difficult to be handled [1].